PRODUKTIVITAS DAN BIAYA REKAYASA MESIN PEMBUAT SERPIH KAYU YANG MUDAH DIPINDAH - Wesman Endom (BRIN Publishing, 2013)
A prototype mobile chipper was built to convert small logs (diameter less than 20 cm). Testing runs were undergone inthe village of Cipari, Sub District of South Sukanegara, Cianjur and Sub District of Sadang Purwakarta. Performanceof the chipper much better than the-I type which could convert the waste into chips in average capacity of about 582kg/hour. The owning and operation costs of wood chipper was about Rp 62,929/hour, with operation cost Rp 108/kg.The owing and cost operation using the type-1 prototype chipper was about Rp 249/kg. Cost analysis using rental cost Rp125/kg, the NPV is achieved at about Rp 13.209.928 with IRR at about 30%.